Political Law Of Relocation The Capital Of The Republic Of Indonesia In The Perspective Of National Defense - Fajra, Ilham Jodia; Indra, Mexsassai; Junaidi, Junaidi (Peneliti.net, 2024)
This research aims to explain the legal politics and success of moving the capital city of the Republic of Indonesia from Java to Kalimantan in maintaining state sovereignty. The data used in this research comes from literature in the form of print and electronic media. The results show that the relocation of the Indonesian National Capital is a strategic step based on a strong legal basis, consensus between government institutions, and participation of people's representative institutions in responding to the development of increasingly complex threats, including non-military threats involving various aspects. In this effort, integration with the concept of sishankamrata, involving intelligence, defense, security, and cyber components, supported by the principles of constitutionalism, checks and balances, and participation across state institutions is important to maintain harmony in Indonesia's constitutional system. While the relocation of the capital city is an ambitious move with significant impacts on defense, the economy and the constitution, the government's steps taken to date reflect a determination to ensure success and constitutional sovereignty in this process. The success of the new capital city in safeguarding the country's sovereignty relies heavily on careful implementation, good inter-agency coordination, and transparency in the use of public resources, with the need for further evaluation as the move nears full implementation, especially in the case of the new capital city.